Detection and analysis of energy data by using quantum filter - Haohan WU; Gang JIANG (Dianxin kexue)
With the rapid development of smart power grid as the core of smart meters,power big data has attracted the attention of users,power companies and the government.The introduction of adaptive filtering into the power grid information monitoring was explored.Due to the complexity of the power load curve,specific model cannot be described.A model-independent intelligent filter was constructed by using the recurrent quantum neural network.The quantum filter was tried to use in the power load forecasting and abnormal electrical testing.